PELATIHAN KEMAMPUAN MENDESKRIPSIKAN TEMPAT WISATA TANJUNG BASTIAN DALAM BAHASA INGGRIS MASYARAKAT PESISIR PANTAI WINI PERBATASAN NKRI-RDTL - Desta Gloria Siahaan; Edmundus Bouk; Marianus Nino; Sherli Metriana Aoetpah; Yohanes Klaes; Maria Imaculata Amloki; Arlando Boifala (Fakultas Teknik, Universitas Bangka Belitung, 2022)
The community service of the English Speaking Skill Training for the Wini Coastal Community at the NKRI-RDTL border was carried out by a service team, namely lecturers and university students from the University of Timor. Wini Beach is located in North Insana District, North Central Timor Regency, East Nusa Tenggara. The training was held for 3 days at the Hamusu Wini Village Office and Community Center. The method used in this training is speaking test of Describing Tanjung Bastian by guide to foreign tourist. The number of community service participants is 39, coming from various backgrounds, with range of 14 - 40 years old. After the training, it can be concluded that the trainees are able to describe Tanjung Bastian in English. The servicers also suggested that similar training could be carried out to improve the knowledge and fluency of the Wini coastal community in speaking English.